Immune Dysregulation Is Associated with Neurodevelopment and Neurocognitive Performance in HIV Pediatric Populations—A Scoping Review - Monray E. Williams; Anicia Janse Van Rensburg; Du Toit Loots; Petrus J. W. Naudé; Shayne Mason (Viruses, 2021)
HIV-1 is known for its complex interaction with the dysregulated immune system and is responsible for the development of neurocognitive deficits and neurodevelopmental delays in pediatric HIV populations. Considering that HIV-1-induced immune dysregulation and its association with neurodevelopmental and neurocognitive impairments in pediatric populations are not well understood, we conducted a scoping review on this topic. The study aimed to systematically review the association of blood and cerebrospinal fluid (CSF) immune markers with neurocognitive deficits and neurodevelopmental delays in pediatric HIV populations. PubMed, Scopus, and Web of Science databases were searched using a search protocol designed specifically for this study. Studies were selected based on a set eligibility criterion. Titles, abstracts, and full texts were assessed by two independent reviewers. Data from the selected studies were extracted and analyzed by two independent reviewers. Seven studies were considered eligible for use in this context, which included four cross-sectional and three longitudinal studies. An average of 130 (±70.61) children living with HIV, 138 (±65.37) children exposed to HIV but uninfected and 90 (±86.66) HIV-negative participants were included across the seven studies. Results indicate that blood and CSF immune markers are associated with neurocognitive development/performance in pediatric HIV populations. Only seven studies met the inclusion criteria, therefore, these limited the number of significant conclusions which could have been made by using such an approach. All considered, the evidence suggests that immune dysregulation, as in the case of adult HIV populations, also has a significant association with neurocognitive performance in pediatric HIV populations.